MENINGKATKAN KEMAMPUAN INTERPERSONAL PADA ANAK USIA 5-6 TAHUN MELALUI KEGIATAN KERJA KELOMPOK - Iting, Andi (EDUCHILD (Journal of Early Childhood Education), 2022)
AbstractThis study discusses improving interpersonal skills in children aged 5-6 years through group work activities at Nurharmila Kindergarten, Lamurukung Village, Tellu Siattinge District, Bone Regency. The purpose of this study was to determine interpersonal skills in children aged 5-6 years and to describe the implementation of group work activities in improving interpersonal skills in children aged 5-6 years. Researchers used qualitative research methods, with descriptive analysis. Data collection techniques used are observation, interviews, and documentation. Based on the results of the study, it was concluded that children's interpersonal abilities at the age of 5-6 years are still not optimally developed because children's environmental backgrounds are different so that they affect children's interpersonal abilities. The implementation of group work activities in improving the interpersonal skills of children aged 5-6 years at Nurharmila Kindergarten, Lamurukung Village, Tellu Siattinge District, Bone Regency went smoothly where at the beginning of the implementation, group B teachers were still overwhelmed, but over time, the implementation of activities This group work runs smoothly and is carried out every day by the group B teacher so that the results can be seen that children will become close and interact with their classmates and even this interpersonal ability occurs not only in group work but also during breaks and in the learning process